Assessment of the Procedural Gases Influence at Turning Technology - Ledvina, Miloslav; Dvořáčková, Štěpánka (Manufacturing Technology Journal, 2016)
This paper deals with the assessment of the procedural gases progressive cooling methods and cooling by procedural liquids at turning technology on the final workpiece surface quality. Turning by using liquefied CO2, liquefied nitrogen and subcooled air supplied through the vortex tube was compared with the turning without process medium (taken as reference conditions) and with two procedural liquids EOPS 1030 and HOCUT 795 B. At evaluation effect of procedural gases there were monitored acting forces, cutting tool cooling rate and the machined layer of the material, cutting tool durability and cut surface quality which was characterized by surface roughness and dimensional accuracy. During the experimental part there were used devices as lathe SU50, piezoelectric dynamometer, the evaluation unit and profilometer. This issue was solved within solving the project TACR - TA03010492.
Keywords: Turning; Cooling by Gas; Acting Forces; Tool Durability; Temperature; Surface Quality